Diagnostic possibilities of determination of osteogenesis disorders in children born with low body weight - Shumna, T. Ye.; Levchuk-Vorontsova, T. O.; Шумна, Таміла Євгенівна; Левчук-Воронцова, Тетяна Олегівна; Шумная, Т. Е.; Левчук-Воронцова, Т. О. (My University, 2020)
The work aims at studying the bone tissue mineral density in children born with low body weight, taking into account the dependence on the nature of feeding and polymorphism of the C/A gene polymorphism of COL1A1_1 collagen gene (rs1107946). Materials and methods. The study involved 74 children. Of these, 29 children born with the body weight of 1500-1999 g were in the observation group I; 25 children weighing 2000-2499 g - group II; 20 children with the body weight at birth of 2500 g - group III (control group). All children were under inpatient treatment at the Municipal Non-Profit Enterprise "City Children Hospital no. 5" of Zaporizhia City Council. Data on the type of breastfeeding of a child aged under 1 year were analyzed for all children. The study of bone tissue mineral density was performed at the age of 12-15 months using an ultrasonic bone sonometer (densitometer) Sunlight MINIOMNI) BeamMed Ltd., Israel. The examination was conducted at the Department of Faculty Pediatrics of the Zaporizhia State Medical University. Analysis of the results was performed by non-parametric statistics methods using the Statistica 13 software package. Ordinal descriptive statistics was used to calculate the average Z-score indicators. The non-parametric statistical method "2 × 2 Table", the Chi-square (df = 1) was used to compare the frequencies of desitometry indicators in different groups. Мета роботи. Вивчення мінеральної щільності кісткової тканини у дітей, що були народжені з малою масою тіла з урахуванням в залежності від характеру вигодовування та поліморфізму гену С / А гена колагену COL1A1_1 (rs1107946). Матеріали та методи. У дослідженні взяли участь 74 дитини. З них 29 дітей, що були народжені за масою тіла 1500-1999г склалось І групу спостереження; 25 дитини з масою тіла 2000-2499 - ІІ групу; 20 дитини з масою тіла 2500г - склалось ІІІ групу, або групу контролю. Всі діти знаходились на стаціонарному лікуванні в Комунальному неприбуткових підприємстві «Міська дитяча лікарня № 5» Запорізької міської ради. У всіх дітей були проаналізовані дані стосовно виду вигодовування дитини до 1 року. Вивчення мінеральної щільності кісткової тканини проводилося у віці 12-15 місяців з використанням ультразвукового кісткового сонометра (денситометра) «Sunlight MINIOMNI») BeamMed Ltd., Ізраїль. Обстеження проводилося на кафедрі факультетської педіатрії ЗДМУ. Аналіз результатів був виконаний з використанням методів непараметричної статистики з допомогою пакету програм Statistica 13. Для обчислення середніх показників Z-score була використана ordinal descriptive statistics. Для порівняння частот показників денситометрії в різних групах використовували непараметричний статистичний метод «2 × 2 Table », the Chi-square (df = 1). Целью работы является изучение минеральной плотности костной ткани у детей, рожденных с низкой массой тела с учетом характера вскармливания и полиморфизма гена C / A гена коллагена COL1A1_1 (rs1107946). Материалы и методы. В исследовании приняли участие 74 ребенка. Из них 29 детей, которые были рождены за массой тела 1500-1999г составили I группу наблюдения; 25 ребенка с массой тела 2000-2499 - II группу; 20 ребенка с массой тела 2500г – вошли в III группу, или группу контроля. Все дети находились на стационарном лечении в коммунальном неприбыльном предприятии «Городская детская больница № 5» Запорожского городского совета. У всех детей были проанализированы данные о виде вскармливания до 1 года. Изучение минеральной плотности костной ткани проводилось в возрасте 12-15 месяцев с использованием ультразвукового костного сонометра (денситометра) «Sunlight MINIOMNI») BeamMed Ltd., Израиль. Обследование проводилось на кафедре факультетской педиатрии ЗГМУ. Анализ результатов был выполнен с использованием методов непараметрической статистики с помощью пакета программ Statistica 13. Для вычисления средних показателей Z-score была использована ordinal descriptive statistics. Для сравнения частот показателей денситометрии в разных группах использовали непараметрический статистический метод «2 × 2 Table», the Chi-square (df = 1).
Діагностичні можливості визначення порушень остеогенезу у дітей, народжених з малою масою тіла
Диагностические возможности определения нарушений остеогенеза у детей, рожденных с низкой массой тела
Keywords: діти, що народжені з малою масою тіла; передчасно народжені діти; денситометрія; остеопороз; остеопенія; грудне вигодовування; штучне вигодовування; змішане вигодовування; поліморфізм гену С / А гена колагену COL1A1_1 (rs1107946); дети, рожденные с низкой массой тела; преждевременно рожденные дети; денситометрия; остеопороз; остеопения; грудное вскармливание; искусственное вскармливание; смешанное вскармливание; полиморфизм гену С / А гена коллагена COL1A1_1 (rs1107946; children born with low body weight; premature babies; densitometry; osteoporosis; osteopenia; breastfeeding; artificial feeding; mixed feeding; C/A gene polymorphism of COL1A1_1 collagen gene (rs1107946)